2009
DOI: 10.1002/cncr.24208
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic cutaneous squamous cell carcinoma of the head and neck

Abstract: BACKGROUND:The authors propose a prognostic score model using a prospective study of patients with regional metastatic cutaneous squamous cell carcinoma of the head and neck.METHODS:Two‐hundred fifty patients were analyzed using a competing risks model to identify risk factors for survival. A risk score was obtained using the significant coefficients from the regression model, and cutoff points were determined that separated the score into 3 risk groups (low risk, moderate risk, and high risk).RESULTS:At a med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(38 citation statements)
references
References 34 publications
3
34
0
1
Order By: Relevance
“…Considerable attention has been given to assessing the systemic mechanisms mediating immune suppression in cancer patients such as those with HNSCC and, in particular, emphasis has been placed on measurement of immune inhibitory cytokines [2225]. However, less is known about the intratumoral immune status and little is known about the immunological milieu in premalignant oral lesions.…”
Section: Resultsmentioning
confidence: 99%
“…Considerable attention has been given to assessing the systemic mechanisms mediating immune suppression in cancer patients such as those with HNSCC and, in particular, emphasis has been placed on measurement of immune inhibitory cytokines [2225]. However, less is known about the intratumoral immune status and little is known about the immunological milieu in premalignant oral lesions.…”
Section: Resultsmentioning
confidence: 99%
“…However, survival rates remain at less than 50% in HNSCC due to disease recurrence and the development of distant metastases (2). It has been suggested that CRT eliminates subsets of immune cells, thus reducing anti-tumor effector functions and contributing to disease recurrence (3).…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] There are numerous case reports of cSCC of the head and neck (cSCC-HN) with virulent clinical courses, and studies have shown that immunosuppressed patients with cSCC-HN more frequently exhibit high-risk pathologic features. 9,10,[13][14][15][16][17][18] However, there is a paucity of data addressing comparative outcomes in this particular patient population. Whether recurrence risks are higher in immunosuppressed patients with cSCC-HN compared with immunocompetent patients is unclear.…”
mentioning
confidence: 97%